Osteosarcoma Biology, Behavior and Mechanisms - Honoki, Kanya; Richard Weiss, Kurt (IntechOpen, 2017)
Osteosarcoma is the most common malignant bone tumor and mainly affects children, adolescents, and young adults. Osteosarcoma shows significant genetic instability, resulting in very complex biology with multifaceted cellular and molecular mechanisms and behavior. Although clinical outcomes, both prognostic and functional, of osteosarcoma dramatically improved in the 1980s, the prognoses of the patients with relapsed and/or metastatic disease remained very poor in spite of our continuous efforts to overcome this difficulty. This book aims to delve into the current advances of basic and clinical sciences in osteosarcoma that are guiding the future directions of its research and clinical practice. The knowledge presented here will lead to further inspiration, ideas, and novel insights into the field of osteosarcoma research. Hopefully, this work will foster improvement of the prognosis for patients suffering from the disease.